Ceramide Metabolism and Parkinson’s Disease—Therapeutic Targets - Antía Custodia; Marta Aramburu-Núñez; Clara Correa-Paz; Adrián Posado-Fernández; Ana Gómez-Larrauri; José Castillo; Antonio Gómez-Muñoz; Tomás Sobrino; Alberto Ouro (Biomolecules, 2021)
Ceramide is a bioactive sphingolipid involved in numerous cellular processes. In addition to being the precursor of complex sphingolipids, ceramides can act as second messengers, especially when they are generated at the plasma membrane of cells. Its metabolic dysfunction may lead to or be a consequence of an underlying disease. Recent reports on transcriptomics and electrospray ionization mass spectrometry analysis have demonstrated the variation of specific levels of sphingolipids and enzymes involved in their metabolism in different neurodegenerative diseases. In the present review, we highlight the most relevant discoveries related to ceramide and neurodegeneration, with a special focus on Parkinson’s disease.